Remodel of [formerly Hass] house for Mr. and Mrs. Jack Foster, floor plan, sheet no. 2 - Mark Mills::::::::: (1969)
Originally drawn for the Hass house (175-4-c-ff216-01) in 1969, parts of this drawing were erased and re-drawn for the remodel project in 1979.